Estabilização do carbono- 13C de resíduos culturais no solo afetada pela qualidade, manejo dos resíduos e teor de carbono do solo - Mezzalira, Ana Paula (2020)
Crop residue quality and soil carbon (C) content influence the stabilization of C in the granulometric fractions of soil organic matter (SOM). However, little is known about the interactions between these factors and under different management conditions and the amounts of crop residue added to the soil on the dynamics of decomposition and stabilization of C in the soil. The aim of this study was to evaluate the effect of the quality and quantity of the residue, soil management and the initial C content of the soil on the stabilization of C in the soil. In a 360-day field study, residues from shoots and roots of soybean and grain sorghum labelled with 13C were used in a Typic Paluedalf with different initial levels of C content. The shoots residues were applied on the surface and incorporated into the soil at rates of 4 and 8 Mg ha-¹ while root residues were incorporated into the soil only at the rate of 4 Mg ha-¹. Remaining C in the residues and in the soil at 30, 180 and 360 days were evaluated. At 360 days, the physical particle size fractionation of the SOM (<53μm and >53μm) was carried out to evaluate the stabilization efficiency index (SEI) of C in the soil. At 360 days there was no interaction between soil C content and crop residue type on the decomposition and recovery of C in the soil and in the fraction <53μm. The soil C content of the soil affected the residue-C recovered in the fraction <53μm, which was higher in the soil with low C content. The decomposition of soybean shoots was faster than that of sorghum however, the SEI was higher with sorghum residues than with soybean (12 x 8%). The decomposition of soybean roots is low than that of sorghum roots, but they have a higher SEI of C (18 x 11%). The SEI of soybean roots is also higher than the SEI of shoot residues, while with sorghum the roots have a lower SEI than the shoot. The results of the present study indicate that C stabilization is higher in soil with lower C content, but does not depend on the chemical quality of the residues (shoot and roots) and that the efficiency of C stabilization of residues in the soil is not related to high quality crop residues with high decomposition rates. Higher SEI were measured with residues that presented lower degradation rates in the initial decomposition phase, indicating that the gradual decomposition allows a greater stabilization efficiency of the by-products of the extracellular enzymes action and microorganisms.